Submarine groundwater discharge in southern Portugal: Insights from stable isotope signatures - Veiga-Pires, C. (2014)
Submarine Groundwater Discharges (SGD) occur almost all around the world and are considered to be significant contributors of high nutrient concentrations to coastal waters.